Performansi Klasifikasi Dosen Berprestasi Menggunakan Metode Naive Bayes Classifier - Indah Purnamasari; Karnita Afnisari (LPPM Universitas Bina Sarana Informatika, 2018)
Education is a very important thing for all individuals in this world. In a country, the education sector is the most noticed sector because it will greatly affect the progress of the country in the future. To achieve the expected level of education, professional educators are required. The professionalism of educators in Indonesia can be known through the achievement that the system has been established by the government. Educators who are achievers should be rewarded accordingly. It aims to motivate educators to grow high dedication to the realization of intelligent learners and foster a sense of pride in the profession. Educators in college are called lecturers. Achievement of lecturers achievement is a lecturer who implement Tridharma Higher Education that is Education, Research and Service to the community. However, the selection of lecturers with achievements in accordance with the requirements of the award system set by the government certainly is not an easy thing. Therefore, to assist the selection of outstanding lecturers in this study used data mining classification with the method of Naive Bayes Classifier with the results of this study achieves an accuracy of 91.67%